An error analysis of interrogative formation in English written language based on linguistics taxonomy categories - Iqramah, Nauratul; Fitriani, Siti Sarah; Fitrisia, Dohra (Research and Innovation in Language Learning, 2023)
Interrogative sentence is quite important in learning and teaching activity, especially for the students of language education who will be an educator in the future, due to the interrogative sentence is one of assessment tools that used in teaching and learning process through spoken or written. Error may occur in constructing interrogative sentence by both native and no-native speaker. The purpose of this study is to identify the most common errors and to find out the sources of errors of interrogative sentences made by twenty two students of third semester of English education department of Syiah Kuala University. The approach used in this study is a qualitative method. The researcher analyzed the data based on linguistic categories taxonomy by referring to Collins Cobuild classification (2012) and Richards (1970) on source of errors. The results of this research revealed that the most common errors in the students interrogative is Auxiliary. The major source of errors is Intralingual error due to incomplete application of rules. The findings can help EFL lecturers who want to provide appropriate techniques and strategies for their students in teaching interrogative sentence and increase students awareness of the possible errors that they often do.